Pedagogical and psychological features of developing sport tourism-related motivations in future physical education teachers - G‘ofurov Azizbek Umarjonovich (Psychohealth: Scientific Journal of Psychology and Mental Health, 2026)
Purpose: This study aims to examine the pedagogical and psychological factors influencing the development of motivation for sports tourism among future physical education teachers. It highlights sports tourism as an effective educational tool that promotes physical fitness, teamwork, leadership, and professional competence in teacher training programs. Methods: A mixed-method design combining pedagogical, psychological, and empirical approaches was applied to 120 physical education students aged 18–23. The research was conducted in three stages—preparatory, experimental, and analytical—using the Sport Motivation Scale (SMS), structured questionnaires, observations, and reflective diaries. Quantitative data were analyzed statistically, while qualitative data provided insights into emotional and behavioral changes. Results: Findings revealed a significant increase in students’ intrinsic motivation, self-confidence, and emotional engagement after participating in tourism-based learning. Practical outdoor experiences proved more effective than theoretical instruction, while social interaction, teamwork, and supportive guidance from instructors played major motivational roles. Conclusion: Sports tourism fosters psychological resilience, professional readiness, and social cooperation among future teachers. It transforms learning into an emotionally meaningful and self-developing process when guided by pedagogical leadership and experiential methods. Limitation: The study focused on a single institution and lacked longitudinal tracking or in-depth fieldwork beyond one academic term. Contribution: This research contributes to the improvement of teacher education curricula by integrating motivational technologies, experiential learning, and outdoor pedagogy to build competent, motivated, and socially responsible educators.